The Ethics of Animal Use: One Veterinarian’s Perspective - Edling, Thomas M. (Journal of applied animal ethics research, 2019)
Animals have been by our sides since the beginning and continue to be shaped and molded by human actions. We all started on a somewhat equal footing, but now we are not. Animals can still outperform people in every aspect of the physical world such as size, strength, speed, quickness, and eyesight. But, humans have surpassed all animals in the ability to use our thoughts, ideas and physical attributes to change the world. It is a fact that one of the major changes in the world is that humans now use animals in a variety of ways. Veterinarians are called upon to work with animals society has placed in our path and provide them with the best life possible. It is important work that must be done. We veterinarians are uniquely qualified, positioned and ethically bound to use our world changing abilities to bring animals back to the equal moral footing they deserve.